Labour market importance of poor health in the Russian Federation - Yevgeniy Goryakin; Marc Suhrcke (University of East Anglia, Health Economics Group (HEG), 2013)
This paper examines the economic consequences of poor health in the Russian Federation, a country with exceptionally adverse adult health outcomes. In both baseline OLS models, as well as in models with fixed effects, acute ill-health events in Russia generally have much weaker association with the logarithm of hours worked than with labour force participation. However, this analysis ignores people who reported zero hours worked. After including them into the analysis with the help of a two part model, the magnitude of the effect of several health events, especially more serious ones, on hours worked increases dramatically. In addition, people with poor self-assessed health living in rural areas are less likely to stop working, compared to people living in the cities, and, perhaps surprisingly, women are also less likely to stop working than men. While there is no conclusive explanation, it is potentially due to the existence of certain barriers that prevent people with poor health from withdrawing from the labour force easily in order to take care of their health. If this is the case then better social insurance protection mechanisms, including more comprehensive unemployment and health insurance, may be required to alleviate the economic burden of ill health in Russia.
Keywords: 330